Enzymatic specificities and modes of action of the two catalytic domains of the XynC xylanase from Fibrobacter succinogenes S85. - Zhu, H (1994)
The xylanase XynC of Fibrobacter succinogenes S85 was recently shown to contain three distinct domains, A, B, and C (F. W. Paradis, H. Zhu, P. J. Krell, J. P. Phillips, and C. W. Forsberg, J. Bacteriol. 175:7666-7672, 1993). Domains A and B each bear an active site capable of hydrolyzing xylan, while domain C has no enzymatic activity. Two truncated proteins, each containing a single catalytic domain, named XynC-A and XynC-B were purified to homogeneity. The catalytic domains A and B had similar pH and temperature parameters of 6.0 and 50 degrees C for maximum hydrolytic activity and extensively degraded birch wood xylan to xylose and xylobiose. The Km and Vmax values, respectively, were 2.0 mg ml-1 and 6.1 U mg-1 for the intact enzyme, 1.83 mg ml-1 and 689 U mg-1 for domain A, and 2.38 mg ml-1 and 91.8 U mg-1 for domain B. Although domain A had a higher specific activity than domain B, domain B exhibited a broader substrate specificity and hydrolyzed rye arabinoxylan to a greater extent than domain A. Furthermore, domain B, but not domain A, was able to release xylose at the initial stage of the hydrolysis. Both catalytic domains cleaved xylotriose, xylotetraose, and xylopentaose but had no activity on xylobiose. Bond cleavage frequencies obtained from hydrolysis of xylo-alditol substrates suggest that while both domains have a strong preference for internal linkages of the xylan backbone, domain B has fewer subsites for substrate binding than domain A and cleaves arabinoxylan more efficiently. Chemical modification with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide methiodide and N-bromosuccinimide inactivated both XynC-A and XynC-B in the absence of xylan, indicating that carboxyl groups and tryptophan residues in the catalytic site of each domain have essential roles.